Posted by **Sashaank** on Wednesday, November 17, 2010 at 3:33am.

2. Find the LCM and GCD of (2y^2 - 3a^2)x + (2a^2 - 3x^2)y and (2a^2 + 3x^2)y + (2y^2 + 3a^2)x

3.Find m if the polynomials (x^2 - 2mx + 2) and (3x^2 - mx - 4) have a common linear factor

4. The ramainder on dividing 121^n - 25^n + 1900^n - (- 4)^n by 2000 is ___________

5. Find the cubic polynomial such that f(1) is 1 , f(2) is 2, f(3) is 3 and f(4) is 5/

6.If x+a is HCF/GCD of x^2+px+q and x^2+lx+m , then the value of a is ______

7. If x^2+5x+a , x^2+3x+b have a common factor and (a-b)^2 = a(3a-5b) . Find a

## Answer This Question

## Related Questions

- discrete math - If a and b are positive integers, prove that: ab = gcd(a,b)*lcm(...
- math! - GCD (24,20)IS 4. sINCE gcd (4,12) IS 4, THEN gcd (24,20,12) is 4. use ...
- math - GCD (24,20) IS 4. sINCE gcd(4,12 ) is 4 then GCD (24,2012 IS 4 USE ...
- math - Find each of the following (a)GCD (12, 26, 65) (b) LCM (12,26,65)
- math?* - Find each of the following. (a) GCD(12, 26, 65) (b) LCM(12, 26, 65)
- math - if a=2^3*3^7*5^3*11^4 and b=2^2*3^5*7^2*11*13,find the following.(leave ...
- math - If a = 2^3 œ 3^7 œ 5^3œ 11^4 and b = 2^2 œ 3^5 œ 7^2 œ 11 œ 13, ...
- Math - This is a problem concerning GCD. I need to prove gcd(a,b) = gcd(a,b+a). ...
- math-please help - if a=2^3*3^7*5^3*11^4 and b=2^2*3^5*7^2*11*13,find the ...
- math-please help - if a=2^3*3^7*5^3*11^4 and b=2^2*3^5*7^2*11*13,find the ...

More Related Questions